Modifications in the correlation function in poly(vinyl alcohol)/silica hybrid wet gels - Vollet, Dimas R. [UNESP]; Donatti, Dario A. [UNESP]; Ruiz, Alberto Ibanez [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Small-angle X-ray scattering was used to study structural modifications in tetraethoxysilane-derived poly(vinyl alcohol) (PVA)/silica hybrids. The basic structure of the wet gels can be described as a mass-fractal structure with fractal dimension D equal to 2 and characteristic length xi, which increases with addition of PVA. Wet gels with high PVA content exhibit a positive deviation from the mass- fractal power-law scattering at low q; this deviation is associated with additional scattering due to a second large correlation distance zeta, reinforced by the addition of PVA. The fraction of both contributions to the total correlation function was estimated; this is the first time that such a study has been carried out for mass- fractal structures.